2004
DOI: 10.1063/1.1638618
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of the effect of depletion-region modulation on photoconductance lifetime measurements

Abstract: Depletion-region modulation (DRM) has recently been identified as a mechanism that influences photoconductance lifetime measurements. The effect is observed in semiconductor samples containing a depletion-region (i.e., p-n junction solar cells). Experimental measurements presented within demonstrate that the DRM effect dominates the conductance measurement at low excess carrier concentrations, resulting in an overestimation of the effective lifetime by several orders of magnitude. The influence of substrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 7 publications
2
44
0
Order By: Relevance
“…Hence, more likely, the steady-state photoconductance of the a-Si: H͑p + ͒ / c-Si͑n͒ HJ is dominated by depletion-region modulation effects, at low injection. 20,21 Figure 3 shows how the presence of a few nanometer thin intrinsic buffer layer underneath the doped films may affect the surface passivation quality throughout the annealing experiment. Note that for all films of similar dopant type, the deposition-times were exactly the same ͑see Table I͒.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, more likely, the steady-state photoconductance of the a-Si: H͑p + ͒ / c-Si͑n͒ HJ is dominated by depletion-region modulation effects, at low injection. 20,21 Figure 3 shows how the presence of a few nanometer thin intrinsic buffer layer underneath the doped films may affect the surface passivation quality throughout the annealing experiment. Note that for all films of similar dopant type, the deposition-times were exactly the same ͑see Table I͒.…”
Section: Resultsmentioning
confidence: 99%
“…The lifetimes are referred to as effective lifetimes because they include recombination channels due to the implanted atoms, as well as due to Auger recombination, surface recombination and recombination through defects native to the starting material or unintentionally introduced during processing. The apparent increase in effective lifetime at excess carrier densities below 10 14 cm −3 is caused by measurement artefacts [16], and does not reflect the recombination lifetime. In order to compare the impact of the implanted impurities on samples of different dopant densities, we have extracted the effective lifetimes at an excess carrier density corresponding to an injection level of η = 0.1 for the three resistivities studied.…”
Section: Methodsmentioning
confidence: 99%
“…At low injection (Dn < 4 Â 10 13 cm À3 ), the QSSPC measurements are impacted by depletion region modulation (DRM) due to the high charge within the dielectric layers. 64 Since it was shown that PL-based measurements are less sensitive to this effect, 57 QSSPL measurement has an advantage in this range. This advantage is critical for investigations focusing on recombination effects that dominate s eff at low injection.…”
Section: Modellingmentioning
confidence: 99%